2020
DOI: 10.2341/19-144-c
|View full text |Cite
|
Sign up to set email alerts
|

A New Dual-cure Universal Simplified Adhesive: 18-month Randomized Multicenter Clinical Trial

Abstract: Clinical Relevance Non-carious cervical lesion restorations using a dual-cure universal adhesive in self-etch and etch-and-rinse mode showed satisfactory clinical performance after 18 months. SUMMARY Objectives: The objective of this multicenter, double-blind, split-mouth randomized clinical trial was to evaluate the clinical performance of a new dual-cure universal adhesive system (Futurabond U, Voco GmBH) when applied using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Elkaffas et al [27] used the United States Public Health Service criteria, and the authors of the present study used a more sensitive and standardized criteria, known as FDI criteria [44]. This fact justify the report of these defects has been increasingly observed when FDI was used, as observed in previous studies [39,42,45]. However, it is noteworthy that most of these defects are clinically acceptable and easily solved with a repolishing of the restorations [46].…”
Section: Favoreto Mw Et Alsupporting
confidence: 55%
See 1 more Smart Citation
“…Elkaffas et al [27] used the United States Public Health Service criteria, and the authors of the present study used a more sensitive and standardized criteria, known as FDI criteria [44]. This fact justify the report of these defects has been increasingly observed when FDI was used, as observed in previous studies [39,42,45]. However, it is noteworthy that most of these defects are clinically acceptable and easily solved with a repolishing of the restorations [46].…”
Section: Favoreto Mw Et Alsupporting
confidence: 55%
“…Although only short-term clinical data has been reported, the observed success rate should be attributed to the composition of universal adhesive used. Several clinical studies have shown that universal adhesives with ultra-mild/mild pH and containing the acidic functional monomer 10-MDP (10-methacryloyloxydecyl dihydrogen phosphate), such as Futurabond U, yield better clinical results than universal adhesives with a high pH and without 10-MDP [39][40][41][42]. It is noteworthy that all restorations were completed with universal adhesive applied in the self-etch mode associated with the selective enamel etching, because this strategy has shown better clinical performance that only self-etching [30,43].…”
Section: Favoreto Mw Et Almentioning
confidence: 99%
“…The treatment protocols of adhesive-involved restorations were classified as etch-and-rinse (Nr = 1110; number of NCCLs = 964), selective enamel-etching protocols (Nr = 404; number of NCCLs = 358), and self-etch protocols without selective enamel-etching (Nr = 892; number of NCCLs = 746). Most of the trials were of double-blind design, as the clinicians who evaluated the outcomes during follow-ups were blinded, and were not the clinicians who performed the restorations [21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Due to the study design of the 16 RCTs, all trials were under low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a previous meta-analysis suggested that shear bond strength of universal adhesives was improved with prior acid etching of enamel [16]. Since most of the above-mentioned studies were either conducted in relatively short follow-ups, or were of in vitro study designs, for which clinically relevant conclusion cannot be made; moreover, various pathologic conditions of substrates, such as carious or sclerotic dentin, or enamel, may result in varied clinical outcomes [2], t the purpose of this study was to determine the efficacy (≥ 12 months) of three adhesive strategies for restorations using universal adhesives: etch-andrinse, selective enamel-etching, and self-etching without selective etching, through published results of several large-scale randomized controlled trials (RCTs) [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Accordingly, we performed a network meta-analysis on multi-arm [38,39] outcomes from both doubleblind and single-blind RCTs [21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] to compare esthetic, functional, and biological outcomes in terms of World Dental Federation (FDI) criteria and the United States Public Health Service (USPHS) criteria of the three adhesive strategies.…”
mentioning
confidence: 99%
“…Two experienced and calibrated dentists, not involved with the restoration procedures and therefore blinded to the group assignment, evaluated all the restorations once and independently using the World Dental Federation (FDI) [ 33 ] and classical US Public Health Service (USPHS) criteria [ 34 , 35 ] at the baseline and after 6 and 18 months of clinical service. In a case of disagreement between the examiners, a consensus was reached by re-examination and discussion before the patient was dismissed [ 13 , 36 , 37 ]. Only clinically relevant measures for evaluating the performance of the adhesives were used and scored (Tables 2 and 3 ).…”
Section: Methodsmentioning
confidence: 99%